Perencanaan Strategis Sistem Informasi Pada GMIT EFATA SOE Menggunakan Enterprise Architecture Planning (EAP) - Petrus Odeng Saekoko; Johan Jimmy Carter Tambotoh (JURIKOM (Jurnal Riset Komputer), 2022)
GMIT Efata Soe is one of the largest churches located in Soe City, East Nusa Tenggara Province. From the results of interviews conducted, it was found that GMIT Efata Soe has not utilized information systems to support operational activities and still uses manual methods in all work processes. Therefore, this study aims to help optimize operational activities and improve job performance by using the information system at GMIT Efata Soe. The Enterprise Architecture Planning method is a choice of the right method in strategic planning of information systems that can answer the needs of GMIT Efata Soe. Business modeling using value chain analysis gets the business functions of the main and supporting activities that are used as the basis for building a proposed portfolio of systems and applications. From analyzing the main activities and supporting activities, it produces a portfolio of information system applications that can be developed by GMIT Efata Soe in the next few years. The resulting portfolios are GMIT Efata Soe Information System, GMIT Efata Soe Financial Administration Information System, GMIT Efata Soe Archiving Information System, GMIT Efata Soe Employee Information System and GMIT Efata Soe Congregation Information System